Analysis of work and efficiency increase of of the ILUR-03 installation magnetron system for tubular specimens outer surface modification; Journal of Physics: Conference Series; Vol. 830 : Energy Fluxes and Radiation Effects 2016 - Kalin B. A.; Volkov N. V.; Valikov R. A.; Yashin A. S.; Krivobokov V. P. Valery Pavlovich; Yanin S. N. Sergey Nikolaevich; Yuriev Yu. N. Yuri Nikolaevich (Modification of materials with particle beams and plasma flows, 2017)
Title screen